Interaction between dipeptidyl-peptidase-4 inhibitors and drugs acting on renin angiotensin aldosterone system for the risk of angioedema: a pharmacovigilance assessment using disproportionality and interaction analyses - Kannan Sridharan; Gowri Sivaramakrishnan (Diabetology & Metabolic Syndrome)
Abstract Background Dipeptidyl peptidase-4 inhibitors (DPP-4is) and drugs interfering with the renin-angiotensin-aldosterone system (RAAS) are frequently co-prescribed in type 2 diabetes management. Both drug classes have been independently associated with angioedema, raising concerns about potential interaction risks. This study aimed to evaluate the safety signals and interaction patterns for angioedema associated with DPP-4is alone and in combination with RAAS-interfering drugs. Methods We conducted a comprehensive pharmacovigilance analysis using the United States Food and Drug Administration Adverse Event Reporting System (USFDA AERS) database. Disproportionality analyses employing both frequentist (Reporting Odds Ratio, Proportional Reporting Ratio) and Bayesian approaches were performed. Drug-drug interactions were assessed using multiplicative drug-drug interaction model. Additionally, we reviewed published case reports of DPP-4i-associated angioedema. Results Analysis of 29,163,222 reports identified 588 cases of DPP-4i-associated angioedema. Significant safety signals were detected for DPP-4i monotherapies, while combinations with RAAS-interfering drugs demonstrated stronger signals through both frequentist and Bayesian analyses. Significant interaction signals were observed for sitagliptin/irbesartan, sitagliptin/valsartan, linagliptin/valsartan and alogliptin/lisinopril combinations. Alogliptin/lisinopril and sitagliptin/irbesartan combinations showed the highest risk profiles. Angioedema occurred predominantly in elderly patients (> 65 years) and females. Sixteen case reports corroborated the findings from the database assessment. Clinical outcomes were comparable between monotherapy and combination therapy groups. Conclusion This pharmacovigilance analysis reveals significant safety signals for angioedema with specific DPP-4i combinations with RAAS-interfering drugs, suggesting potential drug-drug interactions. These findings emphasize the need for careful patient monitoring, particularly in vulnerable populations, when prescribing these combinations. Further prospective studies are warranted to validate these findings and establish definitive causal relationships.